Innovation and entrepreneurship in Colombia - Molina Romero, Leonardo (Ingeniería Solidaria, 2017)
When I started writing this editorial for the journal Ingeniería Solidaria about innovation and entrepreneurship in Colombia, I wondered why in this country there is no Mark Zuckerberg (founder of Facebook), Steve Jobs (founder of Apple), Bill Gates (founder of Microsoft) or Jack Ma (co-founder of Alibaba), to name some of the most important innovators and entrepreneurs of recent times. Why could they succeed in the United States and China and we cannot do the same in Colombia, where there is so much talent?